Alpha backgrounds in the AMoRE-Pilot experiment - Alenkov, V.; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana (The European physical journal. C, Particles and fields, 2022)
The Advanced Mo-based Rare process Experiment (AMoRE)-Pilot experiment is an initial phase of the AMoRE search for neutrinoless double beta decay of $$^{100}$$Mo, with the purpose of investigating the level and sources of backgrounds. Searches for neutrinoless double beta decay generally require ultimately low backgrounds. Surface $$α $$decays on the crystals themselves or nearby materials can deposit a continuum of energies that can be as high as the Q-value of the decay itself and may fall in the region of interest (ROI). To understand these background events, we studied backgrounds from radioactive contaminations internal to and on the surface of the crystals or nearby materials with Geant4-based Monte Carlo simulations. In this study, we report on the measured α energy spectra fitted with the corresponding simulated spectra for six crystal detectors, where sources of background contributions could be identified through high energy α peaks and continuum parts in the energy spectrum for both internal and surface contaminations. We determine the low-energy contributions from internal and surface α contaminations by extrapolating from the α background fitting model.
Gesehen am 09.02.2023